The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1002/pssa.2210150239
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and thermal properties of ε-Fe2O3

Abstract: ϵ‐Fe2O3 is a phase distinct from other iron oxides and hydroxides. It is antiferromagnetic with TN = 480 °K, and it converts to α‐Fe2O3 at 1040 °K. Mössbauer spectra and magnetic properties of the crystallites studied suggest fine particle behaviour, with a large concentration of vacancies. The magnetically split Mössbauer spectrum has broad lines, even at 4.2 °K, where Hhf = (500 ± 5) kOe, δ = (0.7 ± 0.1) mm/s relative to chromium and 2 ϵ = (0.4 ± 0.1) mm/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 8 publications
5
23
0
Order By: Relevance
“…Trautmann and Forestier (6) reported the preparation of pure -Fe O by boiling an aqueous mixture of potassium ferricyanide, sodium hypochlorite, and potassium hydroxide and heating the precipitate at 400°C. Using similar conditions, De´zsi and Coey (7) To whom correspondence should be addressed. Fax: #33 1 44 27 47 69.…”
Section: -Fementioning
confidence: 88%
See 1 more Smart Citation
“…Trautmann and Forestier (6) reported the preparation of pure -Fe O by boiling an aqueous mixture of potassium ferricyanide, sodium hypochlorite, and potassium hydroxide and heating the precipitate at 400°C. Using similar conditions, De´zsi and Coey (7) To whom correspondence should be addressed. Fax: #33 1 44 27 47 69.…”
Section: -Fementioning
confidence: 88%
“…Viart et al (8) recently obtained fine particles of -Fe O , mixed with hematite, by heating silica xerogels impregnated with a solution of iron nitrate. Transformation of -Fe O into hematite under heating was reported to take place at 500-750°C according to the preparation method (3)(4)(5)(6)(7). Magnetic studies (4,6) of the bulk material concluded to ferrimagnetic properties with a Curie temperature of ca.…”
Section: -Fementioning
confidence: 97%
“…above the  →  transition. This transitions occurs, depending on heating rate and -Fe 2 O 3 crystal size, between 750 and 825°C (Dézi and Coey, 1973;Brázda et al, 2014). A possible conversion to haematite can therefore not be excluded in our case.…”
Section: Discussionmentioning
confidence: 81%
“…As this slope change occurs in both heating and cooling curves it may me associated with the Curie temperature (T C ) of -Fe 2 O 3 , a metastable iron oxide phase with reported T C between 207 and 237°C (e.g. Dézi and Coey, 1973;Popovici et al, 2004;Tuček et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier works, Schrader and Buttner [29] have identified its structure as monoclinic with a = 12.97, b = 10.21, c = 8.44 (in Å) and β =95.66°. Dézsi and Coey [30] report a simpler structure; nevertheless, they also refer to it as ε-Fe 2 O 3 subjected to disorder effects. Tronc, Chanéac and Jolivet [21] have shown that high-temperature heat treatment of γ-Fe 2 O 3 nanoparticles dispersed in silica xerogel gives rise to the formation of ε-Fe 2 O 3 nanoparticles with an average diameter about 30 nm, having orthorhombic structure with a = 5.095, b = 8.789 and c = 9.437 Å.…”
Section: Introductionmentioning
confidence: 99%